The Tale of the Alerion - Guillaume, de Machaut, approximately 1300-1377 (Book collections on Project MUSE., 1994)
With this scholarly translation, Minnette Gaudet and Constance B. Hieatt made this long-neglected narrative poem, the Dit de l'alerion -- a treatise on love and falconry -- available to students of medieval literature.